2007
DOI: 10.1080/10837450701481157
|View full text |Cite
|
Sign up to set email alerts
|

Protein Stability During Freezing: Separation of Stresses and Mechanisms of Protein Stabilization

Abstract: Although proteins are often frozen during processing or freeze-dried after formulation to improve their stability, they can undergo degradation leading to losses in biological activity during the process. During freezing, the physical environment of a protein changes dramatically leading to the development of stresses that impact protein stability. Low temperature, freeze-concentration, and ice formation are the three chief stresses resulting during cooling and freezing. Because of the increase in solute conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
242
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(257 citation statements)
references
References 130 publications
4
242
0
3
Order By: Relevance
“…The difference is explained by the use of a more effective cell lysis procedure and avoidance of repeated freeze/thaw cycles of the cells. Freezing and thawing is a wellstudied stressor of protein stability that promotes denaturation and aggregation [Bhatnagar et al, 2007;Cao et al, 2003].…”
Section: Expression Of Tph2 Variants In Human Cellsmentioning
confidence: 99%
“…The difference is explained by the use of a more effective cell lysis procedure and avoidance of repeated freeze/thaw cycles of the cells. Freezing and thawing is a wellstudied stressor of protein stability that promotes denaturation and aggregation [Bhatnagar et al, 2007;Cao et al, 2003].…”
Section: Expression Of Tph2 Variants In Human Cellsmentioning
confidence: 99%
“…The denaturation during freezing is greater when proteins are frozen under conditions that generate a relatively large ice surface area. The observed results indicate that the freezing rate is an important factor that determines the integrity of lyophilized porous SF membranes 11,23 .…”
Section: Resultsmentioning
confidence: 75%
“…Low temperature and ice formation are some of the stresses resulting during freezing 23 . The differences observed in the integrity of the porous SF membranes may be explained by the influence of the freezing rate.…”
Section: Resultsmentioning
confidence: 99%
“…Repeated freeze-thawing cycling is known to affect the stability of biological samples and, notably, to induce conformational changes in proteins that may ultimately lead to aggregation or degradation. [26][27][28] However, previous studies have shown that some molecules are stable in serum and plasma under conditions of repeated freezing and thawing, even up to 10 cycles. 29,30 The present study showed that even one freeze-thaw cycle led to changes in the concentrations of four analytes (AST, GGT, LDH, and BUN); the change in plasma LDH concentration was similar to that seen FIG.…”
Section: Discussionmentioning
confidence: 99%